THE INFLUENCE OF CAREER DEVELOPMENT AND WORK RELATIONSHIP ON EMPLOYEE PERFORMANCE AT FISHERIES AND AGRICULTURE OFFICE MAKASSAR - Imaduddin; Munizu, Musran; Sanusi, Abdullah (Accounting Profession Journal (APAJI), 2024)
The purpose of this researchis a type of quantitative research with the aim of knowing the effect of career developmentiand work relations the performance of employees of the Fisheries and Agriculture Office of Makassar City. The data collection technique used in this research is by distributing questionnaires to 66 respondents as research sample. The data analysis technique used is descriptive statisticalianalysis, multiple linear regression test, Ritest and t-test using statistics through the version of the Statistical Package for the Social Science (SPSS) application version23.The results of this study indicate that career development has a positive and significant effect on the performance of Makassar City Agriculture and Fisheries Service Employees. Work relations have a positive and significant effection the Performance of Makassar City Fisheries and Agriculture Service Employees.